1998
DOI: 10.1143/jjap.37.5659
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrasonic Motor Using a Metal-Ceramic Composite Actuator Generating Torsional Displacement

Abstract: The N = 88 nucleus "'Eu has been studied by Coulomb excitation with 1 6 0 beams, and from the decay of '"Gd using high-resolution y ray spectroscopy. A comprehen'sive level scheme including many new transitions, new levels and spin assignments is established. The results are compared with previous studies and with the predictions of a rotational-model calculation.NUCLEAR REACTIONS 151Eu('60, 160'y), E = 2 5 4 2 MeV: measured E.,; I,.i"/ coin, py coin, o(E;, OJ, DSA. ' 5 1 E~( r , T'), E = 10 MeV; measured c ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…We have developed a Windmill motor design with basically a flat and wide configuration, using a metalceramic composite structure [10,11]. The motor is composed of four components: stator, rotor, ballbearing and housing unit (Fig.…”
Section: Windmill Motormentioning
confidence: 99%
“…We have developed a Windmill motor design with basically a flat and wide configuration, using a metalceramic composite structure [10,11]. The motor is composed of four components: stator, rotor, ballbearing and housing unit (Fig.…”
Section: Windmill Motormentioning
confidence: 99%
“…In addition, Uchino (2008) found that for power outputs less than 30 W, piezoelectric-driven devices perform better in terms of efficiency than electromagnetic motors. Thus, researchers have demonstrated that piezoelectric actuators can theoretically be miniaturized without sacrificing power density and efficiency (Cagatay et al, 2003;Koc et al, 1998). While these motors have produced significant power outputs for their size, the mechanical translation through friction has limited power output.…”
Section: Introductionmentioning
confidence: 99%
“…That is, elastic body composed of the stator has generally the projector to enlarge the displacement in case of plate-type or ring-type USM. These kinds of stators are very complex and expensive [3][4][5]. A novel linear USM is designed for applying to X-Y stage or Z stage in this paper, and it is focused on eliminating the projector of conventional linear USM.…”
Section: Introductionmentioning
confidence: 99%